Role of Major Themes in the Novel Disgrace by J M Coetzee: The Emerged Aspects of Society in the Post-Apartheid South Africa - Manoj Kumar Yadav, Meenakshi Sharma Yadav (International Journal of Advanced Science and Technology, 2020)
J M Coetzee’s novel, “Disgrace” (1999) that won him the Nobel Prize and the second Booker Prize in the Literature. Disgrace portrays the black-brighten picture of the South African society with a different note where the whites are the oppressed and marginalized section of the community, and “where the hunter became the hunted.” The novel presents not only the major thematic kaleidoscopic picture of the hostilities and brutalities which prevail between the whites and the blacks, but it details the following cultural, psychological and political situations also. After the new Constitution for South Africa was adopted in 1994; Disgrace also came under the debate in the parliament of South Africa. The African National Congress party was one of the most prominent anti-apartheid movements led by Nelson Mandela, who was the first post-apartheid elected president of SA in 1994. During the ruling, the party felt and also accepted that the novel Disgrace that presented an accurate pessimistic picture of South Africa in which the thematic focus reveals the race tool that shows poverty, crime, xenophobia, bloodshed, homosexuality, and as the emerged aspects in the Post-apartheid South Africa. The significant themes of the entire novel revolve around the protagonist David Lurie, "FOR A MAN of his age, fifty-two, divorced, he has, to his mind, solved the problem of sex rather well", who is an old Professor of English Communications at a technical university in Cape Town.